UKRAINIAN COSSACK ARMED FORCES: STAGE OF FORMATION AND DECLINE - YURIY, Mykhailo; KHRISTAN, Nazar (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The Ukrainian Cossack armed forces as a purely military formation consisted of land forces and a naval fleet. According to the system of staffing units, their material and technical support, monetary and material maintenance of personnel, as well as the way the Cossacks served, the armed forces of the Zaporozhian Army were not a regular army. However, they were not a situationally convened militia of civilians. In fact, the Ukrainian Cossack armed forces were a military-hierarchical formation staffed on a corporate basis from among the recognized Cossacks, professional soldiers who were accepted into service as volunteers or mobilized by order of the Zaporozhian authorities. The structure of military units and the number of their personnel changed depending on the specific military-political situation, on the availability of human and material resources that the Zaporozhian authorities could use, and also depending onspecific military-political situation, the availability of human and material resources that the Zaporozhian authorities could use, and also depending on the combat missions that the army had to perform. Despite the lack of unification in this area, it was constant that in the Cossack armed forces the main tactical formation remained the regiment, the number of personnel of which ranged from several hundred to several thousand soldiers. The practice of participation of the Cossack army in combat operations during various military campaigns confirmed the generally quite high reliability of the military command system and the organizational structure of the military units of the Zaporozhian Army.